Maturation of hemispheric specialization for face encoding during infancy and toddlerhood. (April 2021) - Chen, Yuhan; Slinger, Michelle; Edgar, J. Christopher; Bloy, Luke; Kuschner, Emily S.; Kim, Mina; Green, Heather L.; Chiang, Taylor; Yount, Tess; Liu, Song; Lebus, Jill; Lam, Samantha; et al.
Highlights: Using infant magnetoencephalography (MEG), study findings show maturational changes to fusiform gyrus (FFG) activity when viewing faces. Earlier right FFG activity to face stimuli is associated with better social and cognitive ability. Stronger right- than left-hemisphere FFG responses to face stimuli are most evident after 1 year of age. Abstract: Little is known about the neural processes associated with attending to social stimuli during infancy and toddlerhood. Using infant magnetoencephalography (MEG), fusiform gyrus (FFG) activity while processing Face and Non-Face stimuli was examined in 46 typically developing infants 3 to 24 months old (28 males). Several findings indicated FFG maturation throughout the first two years of life. First, right FFG responses to Face stimuli decreased as a function of age. Second, hemispheric specialization to the face stimuli developed somewhat slowly, with earlier right than left FFG peak activity most evident after 1 year of age. Right FFG activity to Face stimuli was of clinical interest, with an earlier right FFG response associated with better performance on tests assessing social and cognitive ability. Building on the above, clinical studies examining maturational change in FFG activity (e.g., lateralization and speed) in infants at-risk for childhood disorders associated with social deficits are of interest to identify atypical FFG maturation before a formal diagnosis is possible.